Jati diri perempuan Fakfak dalam tradisi lisan Etnik Mbaham Matta Wuh - Adolina Velomena Lefaan; Tri Handayani (Universitas Muhammadiyah Malang, 2022)
Each cultural group has values that describe its group identity. The Mbaham Matta Wuh Ethnic Community has philosophical values that explain the identity of Fakfak Women. This research aims to describe the philosophy of life of the Mbaham Matta Wuh ethnic community in seeing women's identity. This research is qualitative with ethnographic methods. Sources of research data are informants, phenomena and documents. The data collection techniques used were interviews, observation and document study. The analysis technique used is descriptive ethnography. Based on the research results, it was found that there is a philosophy in the Mbaham Matta Wuh ethnic community which regulates the conception of custom, religion and government related to the identity of Fakfak women. This philosophy is the philosophy of satu tungku tiga batu, idu-idu maninina jojor, dan henggi. These three philosophies teach life values which guide the lives of the Fakfak people, especially women. All forms of culture in Fakfak society are formed from human awareness of customs, religion and language.